Soreness and ulcers 2: blood diseases and infections - Hassona, Yazan (Henry Stewart Talks, 2017)
Oral ulcers and soreness: main systemic causes, Blood disorders: anemia, hematinics deficiency, hematological malignancies, Infections: viral, bacterial, fungal and protozoal